Thermodynamics of Two-Dimensional Electron Gas in a Magnetic Field. (18th January 2011) - Nizhankovskii, V. I.
Abstract : Change of the chemical potential of electrons in aGaAs-Al x Ga 1 − x As heterojunction was measured in magnetic fields up to 6.5 T at several temperatures from 2.17 to 12.3 K. A thermodynamic equation of state of two-dimensional electron gas well describes the experimental results.